2006
DOI: 10.1002/glia.20416
|View full text |Cite
|
Sign up to set email alerts
|

Cellular iron status influences the functional relationship between microglia and oligodendrocytes

Abstract: Previously, we have reported that there is a spatiotemporal relationship between iron accumulation in microglia and oligodendrocytes during normal development and in remyelination following injury. This in vivo observation has prompted us to develop a cell culture model to test the relationship between iron status of microglia and survival of oligodendrocytes. We found that conditioned media from iron-loaded microglia increases the survival of oligodendrocytes; but conditioned media from iron loaded activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 67 publications
9
134
0
Order By: Relevance
“…This is supported by the evidence that wild-type mice treated with the iron chelator, starting the day after contusion injury, exhibit improvement in locomotor recovery between 3 and 6 weeks after injury that coincides with the period when iron staining is reduced in these macrophages. We cannot rule out the possibility that some of the iron that comes out of these macrophages is safely bound to secreted ferritin (Zhang et al, 2006). Our results with the chelator suggest that at least some of the released iron is redox active and chelatable, which is consistent with reports studying iron release from macrophages after erythrophagocytosis (Moura et al, 1998;Knutson et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…This is supported by the evidence that wild-type mice treated with the iron chelator, starting the day after contusion injury, exhibit improvement in locomotor recovery between 3 and 6 weeks after injury that coincides with the period when iron staining is reduced in these macrophages. We cannot rule out the possibility that some of the iron that comes out of these macrophages is safely bound to secreted ferritin (Zhang et al, 2006). Our results with the chelator suggest that at least some of the released iron is redox active and chelatable, which is consistent with reports studying iron release from macrophages after erythrophagocytosis (Moura et al, 1998;Knutson et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…In the developing brain, microglia provides ferritin as a trophic factor to oligodendrocytes for myelination (Zhang et al, 2006). In our results, in sporadic occurrence throughouts the brain, a small number of resting microglia and phagocytic microglia were heavily filled with Fe(III)-and Fe(II)-deposits throughout the cell body and processes where lysosomes and the cytosol were strongly stained.…”
Section: ) Microgliasupporting
confidence: 57%
“…A follow-up study revealed that OPC proliferation and OL genesis occurring in response to intraspinal microglia activation was significantly reduced by iron chelation, revealing that available iron is necessary for a maximal pro-oligogenic response of microglial activation [35]. This is in accordance with in vitro evidence showing that the iron status of microglia affects their functional relationship with OPCs [36]. In addition, recent work by our group revealed that OPCs internalize macrophage-derived ferritin both in vivo and in vitro, suggesting ferritin may serve as a pro-oligogenic signal between macrophages and OPCs (Schonberg and McTigue, personal observation).…”
Section: Microglia Macrophages and Olssupporting
confidence: 79%